City countdown (Albany, N.Y. : The Bureau of Mass Communications, 1981)
Identifies urban problems in developed and developing nations as reflected in the slums of Bangkok, Lima and New York. Analyzes rural migration to urban centers and shows the effect urban poverty has upon the child and family
Title from data sheet
Keywords: Bangkok (Thailand) -- Poor; Lima (Peru) -- Poor; New York (City) -- Poor